Conversion from Off to On-Pump Coronary Artery Bypass Grafting. Is it Avoidable? - Tariq, Khuzaima (Cureus, 2020)
Background With the emergence of new technologies to stabilize the heart off-pump coronary artery bypass grafting (OPCAB), there is an increasing trend that is being observed throughout the world. In certain circumstances, OPCAB needs to be converted to on-pump CABG (ONCAB). In this study, we aim to identify certain risk factors mandating conversions and their associated short-term outcomes. Methods After approval from the institutional ethical review committee and exemption from informed consent, retrospective data of 100 patients meeting the inclusion criteria who underwent OPCAB operations at our institution from August 2018 to July 2019 were included. Preoperative, intraoperative, and postoperative variables were recorded and compared in conversion and non-conversion groups. This study was conducted at the National Institute of Cardiovascular Diseases, Karachi, Pakistan. Results A total of 100 patients were included in this study, out of which 82% (82) were male, with age ranging between 18 and 77 years with a mean age of 56.34 ± 8.3 years. In nine of the cases, OPCAB was emergently converted to ONCAB due to arrhythmias. In nine (9%) cases, off-pump CABG was emergently converted to on-pump CABG (ONCAB). Emergent conversion was due to arrhythmias in five cases, due to hypotension during OM graft in two cases, and due to hypotension during ramus graft for the remaining two cases. The emergent conversion was significantly associated with higher New York Heart Association (NYHA) functional classification and comorbid conditions such as chronic obstructive pulmonary disease (COPD). Conclusion Emergency conversion from off-pump to OPCAB is the most catastrophic event causing higher morbidity and mortality. Conversion rate was observed to be 9% with arrhythmias being the common cause and patients with higher NYHA status and COPD at baseline were found to be at increased risk of emergency conversion. Considering our results in patients with diagnosed COPD and higher NYHA status, the decision for off-pump CABG should be wisely taken carefully weighing the risks and benefits.